Problems with measuring satisfaction with social care. (25th March 2015) - Willis, Rosalind; Evandrou, Maria; Pathak, Pathik; Khambhaita, Priya
Abstract: The measurement of customer satisfaction has become widespread in both healthcare and social care services, and is informative for performance monitoring and service development. Satisfaction with social care services is routinely measured with a single question on overall satisfaction with care, comprising part of the Adult Social Care Survey. The measurement of satisfaction has been problematised, and existing satisfaction measures are known to be under‐theorised. In this article, the process of making an evaluation of satisfaction with social care services is first informed by a literature review of the theoretical background, and second examined through qualitative interviews conducted in 2012–2013 with 82 service users and family carers in Hampshire, Portsmouth and Southampton. Participants in this study were from white British and South Asian backgrounds, and the influence of ethnicity in the process of satisfaction evaluation is discussed. The findings show that the majority of participants selected a positive satisfaction rating even though both positive and negative experiences with services were described in their narratives. It is recommended that surveys provide opportunity for service users and family carers to elaborate on their satisfaction ratings. This addition will provide more scope for services to review their strengths and weaknesses.